Reaching for Epistemic Humility - Lyudmila Bryzzheva (International Journal of Critical Diversity Studies)
Positionality matters. Muscle memories matter. This article traces the journey of a white Russian female scholar from voice, agency, and her ultimate reach toward epistemic humility. I take the reader through formative experiences as an emerging scholar in Soviet Russia and then as an academic researcher with significant epistemic privilege in the United States. My understanding of my scholarly voice grows from no legitimate voice to an inflicted collective voice, to hysterical individualism and then an internally dialogic voice.